The Argumentative System in Qur’anic Discourse: An Analysis of Elements and Interactions - .abdesselam, zouhir (El Omda in Linguistics and Discourse Analysis, 2026)
This study analyzes the Qur'an's argumentative structure through an integrated rhetorical-discursive approach examining linguistic, logical, and contextual dimensions. Findings reveal a unique persuasive system combining rational proofs, emotional appeals, and ethical principles, with adaptive differences between Meccan (theological) and Medinan (legal) discourses. The research demonstrates the Qur'an's distinctive capacity to simultaneously engage reason and emotion while maintaining contextual coherence. These insights advance understanding of Islamic persuasive discourse and its contemporary applications in interfaith communication.